Limit states for the damage assessment of bridges supported on LRB bearings. (June 2015) - Jara, M; Gómez, C; Jara, J M; Olmos, B A
Abstract: There is now a common awareness that excessive strength is neither essential nor a synonymous of good performance in strong earthquakes. It is widely recognized that the design process should put more emphasis on predicting structural damage, according to the performance -based design philosophy. This paper presents an approach for assessing the damage level of lead rubber isolation devices and reinforced concrete piers, according to the performance-based design framework. The proposed performance limit states are based on the control of the materials strain, by means of the shear displacement of the bearing and the hinge rotation of the pier. The performance of the piers of different types of bridges is evaluated with the proposed methodology considering four different limit states.